Minat Mahasiswa Program Studi Pendidikan Olahraga dalam Mengikuti Pembelajaran E-Learning di Universitas Quality Berastagi - Janwar Frihasan Sinuraya; Julius Boy Nesra Bagismata Barus (Mahesa Research Center, 2021)
Learning that is carried out online or online has not been implemented in various universities including Quality Berastagi University. However, the impact of the Covid-19 pandemic, which requires universities to carry out lectures from face-to-face to online using e-learning, has resulted in new habit changes. So it is necessary to do research to the extent that students' interest in participating in the learning. The purpose of this study was to analyze the interest of students in the Sports Education Study Program in participating in e-learning learning at the University of Quality Berastagi. This type of research is descriptive quantitative, the method used is the survey method. The number of samples, namely students of the Sports Education Study Program class of 2019 and class of 2020 who took part in e-learning learning in the odd semester of 2020/2021 were 31 students. Google form is used as a questionnaire tool in the research instrument. Data analysis is used by making in the form of frequency and percentage. The results showed that the students' interest in the Sports Study Program in participating in e-learning was in the medium category (58.06%) as many as 18 students.